Evaluation of a Clinical Service Model for Dysphagia Assessment via Telerehabilitation - Elizabeth C. Ward; Clare L. Burns; Deborah G. Theodoros; Trevor G. Russell (International Journal of Telemedicine and Applications)
Emerging research supports the feasibility and viability of conducting clinical swallow examinations (CSE) for patients with dysphagia via telerehabilitation. However, minimal data has been reported to date regarding the implementation of such services within the clinical setting or the user perceptions of this type of clinical service. A mixed methods study design was employed to examine the outcomes of a weekly dysphagia assessment clinic conducted via telerehabilitation and examine issues relating to service delivery and user perceptions. Data was collected across a total of 100 patient assessments. Information relating to primary patient outcomes, session statistics, patient perceptions, and clinician perceptions was examined. Results revealed that session durations averaged 45 minutes, there was minimal technical difficulty experienced, and clinical decisions made regarding primary patient outcomes were comparable between the online and face to face clinicians. Patient satisfaction was high and clinicians felt that they developed good rapport, found the system easy to use, and were satisfied with the service in over 90% of the assessments conducted. Key factors relating to screening patient suitability, having good general organization, and skilled staff were identified as facilitators for the service. This trial has highlighted important issues for consideration when planning or implementing a telerehabilitation service for dysphagia management.